Macroeconomic and Firm-Level Determinants of Bank Stock Returns: The Role of Interest Rates, Inflation, Profitability, and Firm Size - Steven Adelia; Anggraini Syahputri; Harry Setiawan; Giriati; M. Ridwan Ristyawan (Journal of Educational Management Research, 2026)
This research examines the influence of the BI Rate, inflation, profitability (ROA), and firm size on banking stock returns. The analysis applies a quantitative approach using panel data regression with the Common Effect Model (CEM). The sample consists of 39 banking companies selected through purposive sampling, with observations covering the 2021–2024 period. Secondary data were analyzed using EViews 12 to evaluate the relationship between macroeconomic indicators and firm characteristics on stock returns. The results show that the BI Rate and inflation have a negative and significant effect on stock returns, while firm size has a positive and significant effect. In contrast, profitability (ROA) does not have a significant effect on banking stock returns. Simultaneously, all independent variables significantly influence stock returns, indicating that both macroeconomic conditions and firm characteristics jointly shape investor responses in the capital market. These findings imply that interest rate policy and inflation dynamics are important macroeconomic signals that influence investor behavior, while firm size reflects stability that can attract investment interest. Therefore, investors should consider macroeconomic trends and company scale when making investment decisions, while bank management needs to strengthen financial credibility and transparency to improve market confidence.